Climate change mitigation and adaptation in Bangladesh: The need for community‐based approaches. (5th October 2020) - Roy, Sajal; Sims, Kearrin
Abstract : Climate change is a leading threat to sustainable socio‐economic development in Bangladesh. Adverse impacts of climatic disasters including flash floods, recurrent cyclones and erratic rainfall patterns are already causing hardship for both rural and urban people and are expected to accelerate into the future. The aim of this research note is to identify the core contributing economic sectors to climate change in Bangladesh, and to consider effective mitigation strategies. Following the 5th Assessment Report (AR5) of the Intergovernmental Panel on Climate Change (IPCC) report (2014), in this paper, we argue that comprehensive mitigation measures are required in the energy, transport, buildings, industry and land‐use sectors to reduce Greenhouse Gas (GHG) emissions. Our findings indicate that it is crucial that government and non‐government mitigation efforts engage with community knowledge practices in order to most effectively reduce GHG emissions and combat the adverse impacts of climate change.